ANALISIS ANGGARAN KOMPREHENSIF PADA PERUSAHAAN MANUFAKTUR - Made Adnyana (Jurnal Ilmu dan Budaya, 2010)
Sale planning is a program made to determine the level of sale forthcoming. Meanwhile, forecasting is done in order that the produced analyses could reduce the uncertainties. More over, it is important to make the expense efficiency progress by least square also accountancy and budgeting descriptive methods.